An engraving by E. Therond, published in a French book, c.1887 - E. Therond (Wikimedia Commons, 2008)
Notice iconographique issue de Wikimedia Commons. Titre: An engraving by E. Therond, published in a French book, c.1887. An engraving by E. Therond, published in a French book, c.1887 | CLICK ON THE IMAGE FOR A VERY LARGE SCAN Source: Bought on ebay and scanned by FWP, Sept. 2008
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons